Features of the improved methodology of pedagogical control of physical preparedness of athletes in aesthetic gymnastics - Камаєв, Олег; Осадчиєва, Світлана (Slobozhanskyi Herald of Science and Sport, 2018)
Oleg Kamaev & Svitlana Osadchyieva Purpose: determine the most effective method of pedagogical control of physical prepareness of athletes 12–14 years old, engaged in aesthetic gymnastics. Material & Methods: in the experiment involved twenty athletes 12–14 years old, engaged in aesthetic gymnastics. Theoretical analysis and generalization of scientific and methodical literature was carried out, pedagogical methods of research, medical and biological methods of research, methods of mathematical statistics. Results: the complex of exercises of pedagogical control of physical prepareness of gymnasts at the stage of basic specialized training in aesthetic gymnastics is developed, theoretically and experimentally proved. Conclusions: advanced complex is a rational systematization of the means of pedagogical control in aesthetic gymnastics, which will allow gymnasts to progress and have high results in the sport of higher achievements.